2020
DOI: 10.2217/nnm-2019-0317
|View full text |Cite
|
Sign up to set email alerts
|

Phonophoretic Application of A Glucosamine and Chondroitin Nanoemulsion for Treatment of Knee Chondropathies

Abstract: Aim: This study was performed to assess the effect of the phonophoretic application of a nanoemulsion incorporating glucosamine and chondroitin sulfate (NANO-CG) associated with kinesiotherapy on the reduction of pain and stiffness in knee chondropathy. Materials & methods: NANO-CG was tested in vitro and in vivo prior to being applied in a randomized and controlled clinical trial. Results: Cell viability and hen’s egg test-chorionallantonic membrane tests indicated the NANO-CG is safe for topical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The HET-CAM test has the ability to assess the irritating potential of formulations containing surfactants, as in the case of the nanoemulsions herein studied, having a good correlation with the concentration of the investigated product (Zanatta, 2008;Maciel, 2012). In addition, CAM has a vascularized structure similar to the human conjunctiva, being, therefore, important in the response to irritating formulations and in the appropriate choice of compounds for the preparation of nanoemulsions for topical purposes (Leite, 2018). Several tests can be used to assess eye irritation from test substances: bovine corneal opacity and permeability test, isolated rabbit eye test, isolated chicken eye test, and test of the chicken egg (HET-CAM).…”
Section: Discussionmentioning
confidence: 99%
“…The HET-CAM test has the ability to assess the irritating potential of formulations containing surfactants, as in the case of the nanoemulsions herein studied, having a good correlation with the concentration of the investigated product (Zanatta, 2008;Maciel, 2012). In addition, CAM has a vascularized structure similar to the human conjunctiva, being, therefore, important in the response to irritating formulations and in the appropriate choice of compounds for the preparation of nanoemulsions for topical purposes (Leite, 2018). Several tests can be used to assess eye irritation from test substances: bovine corneal opacity and permeability test, isolated rabbit eye test, isolated chicken eye test, and test of the chicken egg (HET-CAM).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Leite et al conducted a randomized controlled trial of patients with knee cartilage using a nanoemulsion containing glucosamine and chondroitin sulfate (NANO-CG). They observed pain relief and full articular cartilage recovery in some patients treated with NANO-CG; 163 Additionally, Hashemzadeh et al conducted a subgroup trial of two groups of patients taking placebo and nanocurcumin and found that nanocurcumin significantly improved the symptoms of osteoarthritis patients with OA; 164 Furthermore, Shakouri et al used leech saliva extract (LSE) in liposomal gel as a complementary treatment for the relief of signs and symptoms of OA. They found that after 1 month of a LSE liposomal gel administration, patients experienced pain relief and enhanced quality of life.…”
Section: Challenges Associated With and Prospects For The Use Of Nano...mentioning
confidence: 99%
“…For the phonophoretic application of glucosamine and chondroitin in the treatment of knee chondropathies, nanoemulsion (nano CG) has been made and evaluated. Nano CG was previously applied in randomized and controlled clinical trials ( 192 ). In this experiment, patients in arm 1 receive nanoemulsion curcumin orally twice daily for up to 3 months.…”
Section: Drug Delivery Systems Entrapping Natural Bioactive Compounds...mentioning
confidence: 99%